A copper organic phosphonate functionalizing boron nitride nanosheet for PVA film with excellent flame retardancy and improved thermal conductive property. (February 2022) - Chen, Qiang; Wang, Zhengzhou
Highlights: Novel copper ethylene diaminetetrakis-(methylene phosphonate) functionalizing boron nitride nanosheet (Cu-EDTMP@BNNNS) was prepared by in-situ self-assembly method. Surface functionalizing BNNS presented a potential in fabricating multifunctional PVA composite films. The prepared PVA composite film have outstanding flame retardancy, good flexibility, strong mechanical performance, and high thermal conductivity. Abstract: With the rapid development of fifth-generation (5G) communication, the polymeric films with satisfactory flame retardancy and high thermal conductivity have become one of the hot topics in academic research and commercial applications. Herein, novel copper ethylene diaminetetrakis-(methylene phosphonate) functionalizing boron nitride nanosheet (Cu-EDTMP@BNNNS) was prepared by in-situ self-assembly method for reduction in the fire hazards of poly (vinyl alcohol) (PVA) film, as well as the improvement on its thermal conductive and mechanical performances. The good dispersion of 1Cu-EDTMP@1BNNNS in PVA matrix results in a 41-fold enhancement in thermal conductivity (8.4 W m −1 K −1 ) of the 1Cu-EDTMP@1BNNNS/PVA composite film compared to pure PVA film. In addition, the peak heat release rate and total heat release of the PVA composite film are 87.0% and 84.3%, respectively lower than the ones of pure PVA film. Moreover, the as-prepared composite film also possesses good flexibility, and high tensile strength (116 MPa).